Piezoelectric force sensor on metallic wire using semiconductor nanorod array

A piezoelectric sensor using semiconductor nanorods on a metal wire substrate addresses the need for precise pressure measurement in catheter procedures, enhancing safety and accuracy by converting force into electrical signals.

KR103044222B1Active Publication Date: 2026-11-05SEOUL NATIONAL UNIVERSITY R&DB FOUNDATION
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020240152744
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2026-11-05
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

Existing catheter-based PCI procedures lack precise pressure measurement capabilities, leading to potential vessel damage due to inadequate force sensing, necessitating an improved force sensor for enhanced safety and accuracy.

Method used

A piezoelectric sensor using a metal wire substrate with semiconductor nanorods and a metal thin film, capable of converting physical force into electrical signals, integrated into a catheter for accurate force measurement.

Benefits of technology

The sensor provides high sensitivity and stable force measurement, improving the reliability and safety of catheter procedures by preventing vessel perforation and trauma.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112024119593873-PAT00001_ABST
    Figure 112024119593873-PAT00001_ABST
Patent Text Reader

Abstract

The present invention relates to a piezoelectric sensor comprising: a metal wire substrate; a piezoelectric material nanorod formed on the metal wire substrate; and a metal thin film deposited on the tip of the piezoelectric material nanorod. The piezoelectric sensor according to the present invention exhibits very high sensitivity and provides stable and accurate force measurement. Furthermore, when using a nanorod array, it has the advantage of improving the reliability of the sensor by ensuring excellent reproducibility of the measurement values. In addition, since it can be fabricated on flexible substrates such as metal wires or 2D material substrates, large-scale manufacturing is possible, making it useful for commercialization. Moreover, wider applications can be expected in next-generation electronics such as medical devices, wearables, and smart devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a piezoelectric sensor of a metal wire using semiconductor nanorods. Background Technology

[0002] Percutaneous Coronary Intervention (PCI) is a minimally invasive procedure used to treat heart disease, particularly coronary artery disease, to widen narrowed or blocked coronary arteries and improve blood flow. The procedure begins by inserting a catheter through a small incision in the femoral artery or the radial artery at the wrist. Contrast agent is then injected through the catheter to image the blood vessels, allowing for the precise identification of the narrowed area. If a narrowing is detected, the affected area is expanded using a balloon attached to the catheter. In many cases, a stent is inserted after the vessel has been expanded with the balloon to stabilize it and prevent it from narrowing again.

[0003] This procedure is suitable for patients with cardiovascular diseases such as angina or myocardial infarction. PCI is less invasive than open-heart surgery, placing less physical burden on the patient and offering a shorter recovery period. It has the advantage of allowing for a quick return to daily life after typically one to two days of hospitalization.

[0004] However, catheter-assisted PCI entails inherent risks, including thrombosis, perforation, and other lumen damage to the blood vessels. During catheter-based surgery, physicians rely solely on X-ray images for visual guidance to navigate the catheter through the blood vessels. Since X-ray images are typically black-and-white and may lack clarity to depict the condition of the catheter and blood vessels—especially when contrast is low—it was necessary to measure the pressure applied by the catheter to the affected area and perform the procedure accordingly. In particular, for catheters used in delicate areas such as blood vessels, failure to precisely measure the pressure applied by the catheter to the vessel has resulted in medical accidents caused by penetrating the vessel.

[0005] Therefore, various types of sensors are being proposed to measure the pressure applied to the tip of a catheter. Currently, force sensors generally utilize electrical pressure-sensing elements in which the output current changes depending on the externally applied force.

[0006] However, the force sensor using the aforementioned electrical pressure-sensing element has the problem that the change in output current is not significant when a minute external force is applied, and expensive equipment is required to precisely measure the change in current. Therefore, there is a need for an improved force sensor and a catheter utilizing it that can enhance the safety and accuracy of catheter insertion procedures.

[0007] While conducting research to solve the above-mentioned problem, the applicant developed a piezoelectric sensor of a metal wire using semiconductor nanorods and a catheter using the same, thereby completing the present invention. Prior art literature

[0008] Republic of Korea Registered Patent Publication No. 10-0778555 Republic of Korea Published Patent No. 10-2010-0127815

[0009] Miniaturized Piezo Force Sensor for a Medical Catheter and Implantable Device, ACS Appl. Electron. Mater. 2020, 2, 2669-2677 The problem to be solved

[0010] The problem that the present invention aims to solve is to provide a piezoelectric sensor of a metal wire using semiconductor nanorods and a catheter using the same.

[0011] Meanwhile, the technical problems of the present invention are not limited to those mentioned above, and other unmentioned technical problems will be clearly understood by a person skilled in the art from the description below. means of solving the problem

[0012] The present invention comprises a metal wire substrate;

[0013] Piezoelectric material nanorods formed on the metal wire substrate; and

[0014] A piezoelectric sensor comprising a metal thin film deposited on a piezoelectric material nanorod is provided.

[0015] In addition, the present invention provides a catheter comprising the piezoelectric sensor.

[0016] In addition, the present invention provides a method for manufacturing a piezoelectric sensor comprising: (A) synthesizing piezoelectric material nanorods on a metal wire substrate; and (B) depositing a metal thin film on the nanorods. Effects of the invention

[0017] The piezoelectric sensor according to the present invention exhibits very high sensitivity and provides stable and accurate force measurement. Furthermore, when using a nanorod array, the reproducibility of the measurement values ​​is excellent, which has the advantage of improving the reliability of the sensor.

[0018] In addition, since it can be fabricated on flexible substrates such as metal wires and 2D material substrates, large-scale manufacturing is possible, making it useful for commercialization, and furthermore, wider applications can be expected in next-generation electronics such as medical devices, wearables, and smart devices.

[0019] Meanwhile, the effects of the present invention are not limited to those mentioned above, and other unmentioned technical effects will be clearly understood by a person skilled in the art from the description below. Brief explanation of the drawing

[0020] Figure 1 is a schematic diagram showing the structure of a piezoelectric sensor according to the present invention. FIG. 2 is a schematic diagram showing the structure of a piezoelectric sensor including a nanorod array according to the present invention. FIG. 3 is a diagram schematically illustrating the principle of a piezoelectric sensor according to the present invention. Figure 4a shows the band edge diagram of the ZnMgO / Au interface under normal conditions. Figure 4b is a diagram showing the band edge diagram of a ZnMgO / Au interface to which an external force is applied. Figure 5 is a diagram showing the step-by-step manufacturing process of a piezoelectric sensor according to the present invention. Figure 6 is a figure showing a manufactured piezoelectric sensor. Figure 7a shows an SEM image of a ZnO / ZnMgO core-shell nanorod array formed on a Ti-wire. Figure 7b shows an EDS mapping image of the elements Zn, Mg, and O of a single ZnO / ZnMgO core-shell nanorod. Figure 7c shows the XRD patterns of ZnO nanorods and ZnO / ZnMgO core-shell heterostructures. Figure 7d shows the low-temperature photoluminescence spectrum of a ZnO / ZnMgO core-shell heterostructure on a Ti-wire. Figure 8 shows an SEM image of an Au-coated ZnO / ZnMgO nanorod array. Figure 9 is a digital photograph of a piezoelectric sensor that has been fabricated and is ready for measurement. FIG. 10 is a schematic diagram showing the electrical connection with the piezoelectric sensor according to the present invention. Figure 11 is a figure showing the IV response of a piezoelectric sensor under normal and static force conditions using a voice coil motor. Figure 12 is a figure showing the periodic force response of the sensor under a static force of 100 mN. Figure 13a is a figure showing the periodic force response of a piezoelectric sensor according to a force that changes over time. Figure 13b is a figure showing the ratio of current fluctuation indicated for a force applied to a piezoelectric sensor. Figure 14 is a figure showing the experimental setup used to measure the force response of the piezoelectric sensor. Figure 15 is a figure showing the contact response between a force sensor and a soft PDMS force stamp. Figure 16a is a figure showing the force response of a sensor to time-varying force using a PDMS force stamp. Figure 16b is a figure showing the linear fit between the force response of the piezoelectric sensor and the applied force. Figure 17 is a figure showing a photograph of a piezoelectric sensor integrated into a catheter tip. Figure 18 is a figure showing the contact force response between a catheter and an artificial blood vessel. Specific details for implementing the invention

[0021] Detailed information regarding the purpose, technical configuration, and resulting effects of the present invention will be more clearly understood through the following detailed description based on the drawings attached to the specification of the present invention. An embodiment according to the present invention will be described in detail with reference to the attached drawings.

[0022] The embodiments disclosed herein should not be interpreted or used to limit the scope of the invention. It is obvious to those skilled in the art that the description including the embodiments herein has various applications. Accordingly, any embodiments described in the detailed description of the invention are illustrative for better explaining the invention and are not intended to limit the scope of the invention to the embodiments.

[0023] As used in the specification, "comprises" and / or "comprising" do not exclude the presence or addition of one or more other components, steps, actions, and / or elements to the mentioned components, steps, actions, and / or elements.

[0024] First, the present invention

[0025] Metal wire substrate;

[0026] Piezoelectric material nanorods formed on the metal wire substrate; and

[0027] A piezoelectric sensor comprising a metal thin film deposited on a piezoelectric material nanorod is provided.

[0028] The structure of a piezoelectric sensor according to the present invention is schematically shown in FIG. 1, and will be explained in detail below.

[0029] The above metal wire substrate is a substrate for the growth of piezoelectric material nanorods, and preferably, the metal wire substrate may be a wire substrate selected from the group consisting of Ti (titanium), Al (aluminum), Ta (tantalum), Ag (silver), Nb (niobium), Cu (copper), Rh (rhodium), Al (aluminum), Cr (chromium), Mo (molybdenum), V (vanadium), and W (tungsten), and more preferably, it may be a Ti wire substrate.

[0030] The above-mentioned piezoelectric material nanorods are formed on the metal wire substrate, and they form ohmic contacts. Ohmic contact refers to an electrical contact where current can ideally flow without resistance; it describes a case where the electrical connection between an electrode and a semiconductor or metal has a linear relationship, and the relationship between voltage and current follows Ohm's Law.

[0031] The above piezoelectric material is preferably zinc oxide (ZnO), zinc oxide / magnesium zinc oxide (ZnO / ZnMgO), gallium nitride (GaN), lead zirconate titanate (PZT; PbZrO3), barium titanate (BaTiO3), aluminum nitride (AlN), and bismuth titanate (Bi4Ti3O). 12 It can be selected from the group consisting of silicon dioxide (Quartz; SiO2), lithium niobate (LiNbO3), potassium sodium niobate (KNN), sodium bismuth titanate (NBT), bismuth ferrite (BFO), polyvinylidene fluoride (PVDF), polyvinylidene fluoride trifluoroethylene (P(VDF-TrFE)), and polyvinyl chloride (PVC), and more preferably zinc oxide / zinc magnesium oxide (ZnO / ZnMgO), wherein the zinc oxide / zinc magnesium oxide may have a coreshell structure.

[0032] Here, the core-shell structure may consist of a zinc oxide (ZnO) core and a zinc oxide magnesium (ZnMgO) shell surrounding it, and the zinc oxide magnesium shell can increase the stability of the core, prevent charge recombination, and reduce reactivity at the surface to improve durability.

[0033] The above piezoelectric material lacks crystal center symmetry and polarizes when an external force is applied. In piezoelectric sensors, nanorods serve as force-sensing elements based on piezoelectric properties.

[0034] The above piezoelectric material nanorods may preferably have a length of 100 nm to 100 μm and a thickness of 10 nm to 10 μm.

[0035] The above piezoelectric material nanorod can be used as a single nanorod or can form a nanorod array containing multiple nanorods, and preferably can form a nanorod array.

[0036] The above nanorod array may be a coaxial structure arranged around the same axis. The structure of a piezoelectric sensor including a nanorod array according to the present invention is schematically shown in FIG. 2.

[0037] The metal thin film is used as an electrode in a piezoelectric sensor and is deposited on the tip of a piezoelectric material nanorod. Preferably, it can be selected from the group consisting of Au (gold), Pd (palladium), Pt (platinum), Ni (nickel), Ir (iridium), Be (beryllium), and Co (cobalt), and more preferably, it can be Au (gold). The metal thin film creates a Schottky contact at the metal-nanorod interface and plays an important role in force detection. When the piezoelectric sensor receives an external force, the Schottky barrier height changes due to piezoelectric charges induced in the metal-nanorod interface region, and this change is recorded as the externally applied force.

[0038] The piezoelectric sensor of the present invention may include an insulating material between a metal electrode and a metal wire substrate, and the insulating material may preferably be selected from the group consisting of polyimide (PI), spin-on glass (SOG), polymethyl methacrylate (PMMA), and polydimethylsiloxane (PDMS), and more preferably may be polyimide. The insulating material fills the gap between the nanorod arrays and electrically separates the metal thin film deposited on the nanorod tips from the metal wire substrate at the bottom.

[0039] The above piezoelectric sensor may further include a layer of graphene or h-BN (hexagonal boron nitride), also known as white graphene, between the nanorod and the metal wire substrate, and preferably may further include a graphene layer. Graphene or h-BN has high mechanical strength, which can increase the structural stability of the piezoelectric sensor, which may be advantageous for the sensor to withstand external pressure or force.

[0040] The piezoelectric sensor according to the present invention is a type of force sensor that converts physical force or pressure into an electrical signal using the piezoelectric effect, and the principle of the piezoelectric sensor according to the present invention is schematically shown in FIG. 3.

[0041] It detects voltage changes resulting from the induction of piezoelectric charges generated when a force is applied. Since the magnitude of the induced piezoelectric charge increases with the applied force and leads to a corresponding increase or decrease in current, it can not only detect the presence of the applied force but also measure its magnitude, allowing it to operate effectively as a force sensor. Specifically, the force response of the sensor is illustrated in Figures 4a and 4b through the band edge diagram of the ZnMgO / Au interface.

[0042] As shown in Figures 4a and 4b, under normal conditions, a Schottky barrier exists at the ZnMgO / Au interface, as confirmed by the IV characteristics, and when an external force is applied, a negative piezoelectric charge is induced at the ZnMgO / Au interface. As mentioned above, this negative charge effectively creates an electron depletion region and increases the height of the Schottky barrier. As the Schottky barrier increases, the current passing through the sensor decreases, which is recorded as a force response.

[0044] In addition, the present invention provides a catheter comprising the piezoelectric sensor.

[0045] The above catheter can measure the force applied to the attachment using the above piezoelectric sensor.

[0046] The above catheter is integrated with a piezoelectric sensor and can be inserted into an artificial blood vessel, detecting contact force while the catheter balloon is inflated.

[0048] In addition, the present invention

[0049] (A) A step of synthesizing piezoelectric material nanorods on a metal wire substrate; and

[0050] (B) a step of depositing a metal thin film on the nanorod; a method for manufacturing a piezoelectric sensor is provided.

[0051] Step (A) above is performed using the metalorganic chemical vapor deposition (MOCVD) method, and a horizontal type system can be used as the MOCVD apparatus, and no metal catalyst is used. The metalorganic chemical vapor deposition method is a very useful chemical vapor deposition method for growing crystal layers to create complex semiconductor multilayer structures, in which high-purity precursor gas is injected into a reactor along with an inert carrier gas and nanorods are grown by coating them onto a flat plate such as a substrate. Preferably, to synthesize zinc oxide / zinc oxide magnesium nanorods, oxygen (O2) and diethylzinc (DEZn) are used as precursors, and argon (Ar) gas can be used as a carrier gas to transport the DEZn.

[0052] The metal wire substrate is a substrate for the growth of piezoelectric material nanorods, and preferably may be a wire substrate selected from the group consisting of Ti (titanium), Al (aluminum), Ta (tantalum), Ag (silver), Nb (niobium), Cu (copper), Rh (rhodium), Al (aluminum), Cr (chromium), Mo (molybdenum), V (vanadium), and W (tungsten), and more preferably may be a Ti wire substrate.

[0053] The above piezoelectric material is preferably zinc oxide (ZnO), zinc oxide / magnesium zinc oxide (ZnO / ZnMgO), gallium nitride (GaN), lead zirconate titanate (PZT; PbZrO3), barium titanate (BaTiO3), aluminum nitride (AlN), and bismuth titanate (Bi4Ti3O). 12 It can be selected from the group consisting of silicon dioxide (Quartz; SiO2), lithium niobate (LiNbO3), potassium sodium niobate (KNN), sodium bismuth titanate (NBT), bismuth ferrite (BFO), polyvinylidene fluoride (PVDF), polyvinylidene fluoride trifluoroethylene (P(VDF-TrFE)), and polyvinyl chloride (PVC), and more preferably zinc oxide / zinc magnesium oxide (ZnO / ZnMgO), wherein the zinc oxide / zinc magnesium oxide may have a coreshell structure.

[0054] The above piezoelectric material nanorods may preferably have a length of 100 nm to 100 μm and a thickness of 10 nm to 10 μm.

[0055] The above piezoelectric material nanorod can be a single nanorod or form a nanorod array including multiple nanorods, and preferably can form a nanorod array.

[0056] The above step (B) is performed by a thermal evaporation process, and the metal can preferably be formed with a thickness of 10 μm or less, and more preferably with a thickness of 100 nm.

[0057] The metal thin film above may preferably be selected from the group consisting of Au (gold), Pd (palladium), Pt (platinum), Ni (nickel), Ir (iridium), Be (beryllium), and Co (cobalt), and more preferably Au (gold).

[0058] The above method for manufacturing a piezoelectric sensor is between steps (A) and (B).

[0059] (a) a step of filling an insulating material between the metal thin film and the metal wire substrate; and

[0060] (b) a step of exposing the nanorod tip through oxygen-containing plasma etching; may be further included.

[0061] The insulating material of step (a) above may preferably be selected from the group consisting of polyimide (PI), spin-on glass (SOG), polymethyl methacrylate (PMMA), and polydimethylsiloxane (PDMS), and more preferably may be polyimide. The insulating material fills the gap between the nanorod arrays and electrically separates the metal thin film deposited on the nanorod tips from the metal wire substrate at the bottom.

[0062] The piezoelectric sensor manufactured according to the present invention exhibits very high sensitivity and provides stable and accurate force measurement. Furthermore, when using a nanorod array, the reproducibility of the measurement values ​​is excellent, which has the advantage of improving the reliability of the sensor.

[0063] In addition, since it can be fabricated on flexible substrates such as metal wires and 2D material substrates, large-scale manufacturing is possible, making it useful for commercialization, and furthermore, wider applications can be expected in next-generation electronics such as medical devices, wearables, and smart devices.

[0065] Below, specific embodiments and experimental examples of the present invention are examined.

[0067] Example 1. Manufacture of a piezoelectric sensor

[0068] The step-by-step manufacturing process of the piezoelectric sensor according to the present invention is shown in FIG. 5.

[0070] 1-1. Fabrication of ZnO / ZnMgO Nanorod Arrays on Ti Wires

[0071] To manufacture the piezoelectric sensor, zinc oxide (ZnO) nanorods were first synthesized from titanium (Ti) wires using the metal-organic chemical vapor deposition (MOCVD) method. Oxygen (O2) and diethyl zinc (DEZn) were used as precursors, and argon (Ar) gas was used as a carrier gas to transport the DEZn. During this process, the MOCVD apparatus was maintained at a temperature of 500°C at a low reactor pressure of 0.8 Torr. To prevent premature reactions, the oxygen gas line was separated from the main gas manifold line.

[0072] After growing ZnO nanorods, cyclopentadienyl magnesium (Cp2Mg) was introduced into the reactor as a magnesium source along with DEZn and oxygen gas under the same conditions, except that the reactor pressure was increased to 5 Torr, to form a uniform ZnMgO shell layer on the ZnO nanorods. The Cp2Mg bubbler temperature was maintained at 40°C and transported to the reactor by Ar gas. The synthesis process was carried out for 30 minutes to grow a ZnO / ZnMgO nanorod array.

[0074] 1-2. Au deposition on polyimide-filled and nanorod arrays

[0075] After growing a nanorod array, the gaps between the nanorod arrays were filled with an insulating polyimide layer using a dip coating method, and then the tips of the nanorod arrays were exposed using oxygen plasma etching. Subsequently, a piezoelectric sensor was fabricated by depositing a 100 nm thick Au layer on the exposed tips of the nanorod arrays using a thermal evaporation process. The fabricated piezoelectric sensor is shown in Fig. 6.

[0077] Experimental Example 1. Confirmation of ZnO / ZnMgO nanorod array formed on Ti-wire

[0078] To confirm the morphology of the core-shell heterostructure of the ZnO / ZnMgO nanorod array formed on the Ti wire prepared in Example 1-1 above, it was first investigated using a field emission scanning electron microscope (FESEM), and the results are shown in Fig. 7a.

[0079] As shown in Figure 7a, it was confirmed through FESEM images that the grown nanorods were densely packed.

[0080] In addition, dispersive X-ray spectroscopy (EDS) was performed on the core-shell heterostructure of the ZnO / ZnMgO nanorod array formed on the Ti wire, and EDS mapping images of the elements Zn, Mg, and O are shown in Fig. 7b.

[0081] As shown in Fig. 7b, it was confirmed that there are no impurity atoms because the elements exhibit a very uniform distribution.

[0082] Next, the crystal structure was confirmed using X-ray diffraction (XRD), and the results are shown in Fig. 7c. The XRD pattern was recorded within the 2-theta range of 30-70 degrees.

[0083] As shown in Fig. 7c, the XRD pattern of the ZnO nanorods exhibits a strong diffraction peak at a 2-theta value of 34.4 degrees, which corresponds to the (002) plane of the hexagonal wurtzite crystal structure of ZnO. Additionally, two other diffraction peaks were observed at 2-theta values ​​of 36.3 degrees and 62.9 degrees, which could be identified as the (101) and (103) planes, respectively. However, the intensity of these peaks is very weak compared to the (002) plane, confirming that the preferred growth direction of the nanorods follows the c-axis. As with the ZnO nanorod array, the XRD pattern of the ZnO / ZnMgO core-shell heterostructure showed a strong diffraction peak at a 2-theta value of 34.5 degrees, which can be identified as the (002) plane of the hexagonal wurtzite crystal structure of the ZnMgO shell. In the case of the core-shell heterostructure, the (002) plane was observed toward a higher 2-theta value, and this slight shift in the XRD peak position can be attributed to the lattice mismatch between the ZnO core and the ZnMgO shell. Through the XRD results, it was confirmed that the ZnO / ZnMgO core-shell heterostructure grown on the Ti-wire is a pure phase and has a c-axis direction preferred, making it suitable for fabricating piezoelectric sensors.

[0084] Finally, low-temperature photoluminescence (PL) of a ZnO / ZnMgO core-shell heterostructure grown on a Ti-wire was performed, and the results are shown in Fig. 7d.

[0085] As shown in Fig. 7d, the PL spectrum exhibits three distinct emission peaks at 3.360 eV, 3.364 eV, and 3.50 eV, respectively. Since the two low-energy peaks of ZnO are closely spaced and the high-energy peak around 3.50 eV originates from the band edge emission of the ZnMgO shell, it was confirmed that the ZnO / ZnMgO core-shell heterostructure was successfully grown on the Ti wire.

[0087] Experimental Example 2. Verification of the structure of the piezoelectric sensor

[0088] As in Examples 1-2 above, Au was deposited on the exposed tip of the nanorod array, and its SEM image was examined, and the result is shown in Fig. 8.

[0089] As shown in Figure 8, it was confirmed that only the tip of the nanorod is well exposed, and the bottom surface of the nanorod is embedded within an insulating polyimide layer that ensures proper insulation between the Top-Au electrode and the bottom Ti-substrate.

[0091] Experimental Example 3. Experiment on Measuring the Force Response of a Piezoelectric Sensor

[0092] To measure the force response, an electrical connection was made between the Top-Au electrode and the bottom Ti-wire using a Cu wire coated with silver paint, as shown in Fig. 9.

[0093] Figure 9 shows a photograph of the device after the manufacturing procedure was completed, which was used to measure the force response.

[0094] First, the force response of the sensor was measured using a voice coil motor. The piezoelectric sensor according to the present invention was firmly attached to a holder, and the direction of the applied force was perpendicular to the sensor surface. A sapphire substrate was used as a pressure stamp to electrically insulate the sensor from the voice coil motor. During the measurement, the upper metal surface of the sensor was subjected to a constant voltage bias, and the lower Ti contact was grounded as shown in FIG. 10.

[0095] Before proceeding with the force response measurement, the IV response of the sensor was investigated by sweeping the voltage from -2v to 2v to confirm the fabrication of the Schottky diode, and the results are shown in Figure 11.

[0096] As shown in Fig. 11, the sensor exhibited rectification under forward bias conditions due to the formation of a Schottky barrier at the ZnMgO / Au interface. After confirming the fabrication of the Schottky diode, the IV response of the sensor was further investigated within a constant applied force range of 200 mN to 1 N. The IV curves indicated that the current passing through the sensor decreased under both forward and reverse bias conditions as the applied force increased. This decrease in current is attributed to the piezoelectric effect, where the externally applied force induces a piezoelectric negative charge at the ZnMgO / Au interface. This induces the formation of electron depletion channels at the ZnMgO / Au interface, resulting in a decrease in current.

[0097] In addition, the force response of the sensor was verified by measuring the current versus time (IT) response for both constant force and time-varying force. During the measurement, a fixed voltage bias of 1.5V was provided to the sensor, and the force response was periodically recorded by applying force, and the results are shown in Fig. 12.

[0098] As shown in Fig. 12, the sensor's IT response under a periodic static force of 100 mN was demonstrated, exhibiting a very stable and reproducible force response. The sensor's rise and fall times were calculated as shown in one of the enlarged cycles in Fig. 12, and the rise and fall times are defined as the time required to reach 90% of the total current change for a given force / release process. The sensor exhibited a fast response time of 200 ms for an externally applied force and a recovery time of 250 ms.

[0099] To further understand the sensitivity of the device, the force response of the sensor was examined under time-varying forces ranging from 60 mN to 300 mN. During each cycle, the force applied to the sensor was increased, and the corresponding response was maintained for 10 seconds. The rate of change of the sensor current as the applied force increased was plotted, and the results are shown in Fig. 13a. Here, the rate of current change is Δ I / I 0= ( I - I 0) / I It is defined as 0, and I and I0 are the currents with and without force applied.

[0100] As shown in Fig. 13a, it was confirmed that the rate of change of the sensor current increases with the applied force. This is because as the applied force increases, more piezoelectric charges are induced at the Au / ZnMgO interface, and consequently, the Schottky barrier height increases, and as a result, the response of the sensor improves as the applied force increases.

[0101] At this time, the ratio of current fluctuation to the force applied to the sensor was shown, and the result is shown in Fig. 13b.

[0102] As shown in Fig. 13b, the linear fit indicated that the device sensitivity was 0.01% / mN.

[0104] Experimental Example 4. Regarding mock blood vessels Experiment to measure the force response of a piezoelectric sensor

[0105] To evaluate the performance of the sensor, it was evaluated under various force conditions using a voice coil motor with a soft PDMS pressure stamp to mimic the contact force between the sensor and the blood vessel, and the experimental setup used to simulate the contact force between the blood vessel and the force sensor is shown in Fig. 14.

[0106] As shown in Fig. 14, the measurement setup was the same as in Experimental Example 3, except that the hard sapphire pressure stamp was replaced with a relatively soft PDMS pressure stamp.

[0107] According to the above settings, the contact response between the force sensor and the soft PDMS pressure stamp was measured under a periodic force of 150 mN, and the results are shown in Fig. 15.

[0108] As shown in Fig. 15, the sensor exhibited a stable and fast force response, confirming its suitability for blood vessel monitoring.

[0109] In addition, the rate of change of the sensor's current under time-variant forces ranging from 50 mN to 500 mN was shown, and the results are shown in Fig. 16a.

[0110] As shown in Fig. 16a, it was confirmed that the rate of change of the sensor's current increases with the applied force. This means that the sensor can prevent perforation and vascular trauma.

[0111] At this time, the ratio of current fluctuation to the force applied to the sensor was shown, and the result is shown in Fig. 16b.

[0112] As shown in Fig. 16b, in the small force range, the sensor sensitivity increases linearly as the applied force increases, whereas the sensor's response begins to saturate when a large force is applied, and it was confirmed that the overall sensitivity in the small force range and large force range is 0.01% / mN and 0.001% / mN, respectively, showing a very stable and fast response.

[0113] Subsequently, a piezoelectric sensor and a catheter were integrated, as shown in Fig. 17. The integrated catheter-integrated force sensor was guided into an artificial blood vessel, and the contact force response between the blood vessel and the sensor was recorded during the expansion and contraction of the catheter balloon, and the results are shown in Fig. 18.

[0114] As shown in Fig. 18, when the balloon inflates, the force sensor comes into contact with the blood vessel wall, and the nanorod array is pressed against the blood vessel wall. Consequently, due to the piezoelectric effect, the current passing through the sensor decreases and is recorded as contact between them. When the sensor, blood vessel, and balloon contract, the sensor loses contact with the blood vessel wall and the current is restored.

[0116] Experimental Example 5. Comparison of Force Sensor Dimensions with Conventional Literature

[0117] The dimensions of force sensors disclosed in conventional literature and the piezoelectric sensor according to the present invention were compared, and the results are shown in Table 1.

[0118] apply Operating principle size literature Monitoring of vascular stiffness piezoelectric Length 3mm Width 1mm Y. Kang, J. Lee, S. Park, J. Kim, S. Il Kim, W. Ryu, ACS Appl. Mater. Interfaces 2023, 15, 17653 cardiovascular monitoring Capacitive Length 20mm Width 7mm Thickness 2.72mm S. Jeon, J. Lee, H. Hwang, W. Ryu, Y. Chae, IEEE Trans. Biomed. Circuits Syst. 2018, 12, 812 cardiovascular monitoring Piezoresistive type Thickness 0.875mm, Diameter 5.6mm Y. Park, H. Luan, K. Kwon, T.S. Chung, S. Oh, J.-Y. Yoo, G. Chung, J. Kim, S. Kim, S. S. Kwak, et al., npj Flex. Electron. 2024, 8, 6. heart resection Intensity modulation Diameter 3mm, Length 18mm P. Polygerinos, A. Ataollahi, T. Schaeffter, R. Razavi, L. D. Seneviratne, K. Althoefer, IEEE Trans. Biomed. Eng. 2011, 58, 721. Cardiac catheter insertion Optical type 3mm in diameter P. Polygerinos, T. Schaeffter, L. Seneviratne, K. Althoefer, in 2009 Annu. Int. Conf. IEEE Eng. Med. Biol. Soc., 2009, pp. 1054-1501. balloon catheter optical fiber Diameter 2.2mm, Length 0.2mm MC Yip, SG Yuen, RD Howe, IEEE Trans. Biomed. Eng. 2010, 57, 1008. Vascular monitoring piezoelectric Diameter 0.127mm The present invention

[0119] In the case of blood vessel monitoring, the device size is very important considering the small size of the blood vessels. The smaller the device size, the easier it is to integrate with a catheter and the safer it can navigate inside the blood vessel. As shown in Table 1 above, it was confirmed that the sensor according to the present invention has the smallest device size compared to conventional literature.

[0120] Although embodiments of the present invention have been described above with reference to the attached drawings, those skilled in the art will understand that the present invention may be implemented in other specific forms without changing its technical concept or essential features. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive.

Claims

Claim 1 A piezoelectric sensor characterized by comprising: a metal wire substrate; a piezoelectric material nanorod having a zinc oxide / zinc magnesium oxide (ZnO / ZnMgO) core-shell structure formed on the metal wire substrate; an insulating layer formed to fill the space between the nanorods, wherein only the tip portions of the nanorods are exposed by plasma etching; and a metal thin film deposited to form a Schottky contact with the exposed tip portions of the nanorods. Claim 2 A piezoelectric sensor according to claim 1, wherein the metal wire substrate is a wire substrate selected from the group consisting of Ti (titanium), Al (aluminum), Ta (tantalum), Ag (silver), Nb (niobium), Cu (copper), Rh (rhodium), Al (aluminum), Cr (chromium), Mo (molybdenum), V (vanadium), and W (tungsten). Claim 3 In claim 1, the piezoelectric material is zinc oxide (ZnO), gallium nitride (GaN), lead zirconate titanate (PZT; PbZrO3), barium titanate (BaTiO3), aluminum nitride (AlN), and bismuth titanate (Bi4Ti3O). 12 A piezoelectric sensor comprising further selected from the group consisting of silicon dioxide (Quartz; SiO2), lithium niobate (LiNbO3), potassium sodium niobate (KNN), sodium bismuth titanate (NBT), bismuth ferrite (BFO), polyvinylidene fluoride (PVDF), polyvinylidene fluoride trifluoroethylene (P(VDF-TrFE)), and polyvinyl chloride (PVC). Claim 4 delete Claim 5 A piezoelectric sensor according to claim 1, wherein the nanorod has a length of 100 nm to 100 μm and a thickness of 10 nm to 10 μm. Claim 6 A piezoelectric sensor according to claim 1, wherein the nanorods form a nanorod array. Claim 7 delete Claim 8 A piezoelectric sensor according to claim 1, wherein the insulating layer is composed of a material selected from the group consisting of polyimide (PI), spin-on glass (SOG), polymethyl methacrylate (PMMA), and polydimethylsiloxane (PDMS). Claim 9 A piezoelectric sensor according to claim 1, wherein the metal thin film is selected from the group consisting of Au (gold), Pd (palladium), Pt (platinum), Ni (nickel), Ir (iridium), Be (beryllium), and Co (cobalt). Claim 10 A piezoelectric sensor according to claim 1, wherein the piezoelectric sensor further comprises a graphene or h-BN (hexagonal boron nitride) layer between a nanorod and a metal wire substrate. Claim 11 A catheter comprising a piezoelectric sensor according to any one of claims 1 to 3, 5 to 6, and 8 to 10. Claim 12 In paragraph 11, the catheter is a catheter that is integrated with a piezoelectric sensor and inserted into an artificial blood vessel. Claim 13 In paragraph 12, the catheter, wherein the piezoelectric sensor detects the force of contact while the catheter balloon is inflated. Claim 14 (A) a step of synthesizing zinc oxide / zinc magnesium oxide (ZnO / ZnMgO) core-shell nanorods on a metal wire substrate; (B) a step of filling an insulating material between the synthesized nanorods to form an insulating layer between a metal thin film and a metal wire substrate; (C) a step of exposing the tips of the nanorods through oxygen-containing plasma etching; and (D) a step of depositing a metal thin film to form Schottky contacts on the nanorods; comprising a method for manufacturing a piezoelectric sensor. Claim 15 A method for manufacturing a piezoelectric sensor according to claim 14, wherein step (A) is performed by a metalorganic chemical vapor deposition (MOCVD) method. Claim 16 delete Claim 17 A method for manufacturing a piezoelectric sensor according to claim 14, wherein the nanorods form a nanorod array. Claim 18 A method for manufacturing a piezoelectric sensor according to claim 14, wherein step (D) is performed by a thermal evaporation process. Claim 19 delete

Citation Information

Patent Citations

  • Piezo-electric nano-generating wearing element using fiber

    KR1020180038250A

  • NANO piezoelectric element

    KR102248482B1

  • High-resolution Parallel-detection Sensor Array Using Piezo-Phototronics Effect

    US20130134440A1